The determinants of intra-regional trade in Southern Africa - Cassim, Rashad (School of Economics, 2015)
This thesis is anchored in policy developments in the Southern African region, including the imminent conclusion of a Southern Africa free-trade agreement (FTA). The major question addressed in the thesis is whether trade integration is achievable and desirable. It does not take for granted that a FTA will automatically induce more trade in the region. The research focuses primarily on trade potential in Southern Africa but also attempts to define why growth in intra-regional trade is not an important objective in its own right. A major aim of this thesis is to quantify the factors that are likely to influence trade growth in Southern Africa. The thesis puts forward a case for more attention to be paid to fundamental structural factors that will determine the scope and success of any regional integration initiative. Various methodologies are employed including an applied review of theoretical work, an analysis and appraisal of current Southern African work and, finally, the estimation of a cross-sectional gravity model of trade. This estimation relies on Tobit maximum likelihood procedures, rather than standard OLS methods. The model uses various data sources, primarily from the IMF and the World Bank. The gravity model examines how the reduction of trade-transaction costs, the level of development and the size of an economy influences trade potential amongst countries. In the thesis, prominence is given to the interpretation of the model and its policy implications. A major finding is that fundamental structural and economic factors such as the transaction costs of trading, the growth paths of economies and changes in per capita income should be the focus of regional integration rather than trade policy in its own right. The empirical results show that intra-regional trade in SADC is not low by international standards. When compared to regions such as SACU or Mercusor, actual South African exports are higher than estimated potential exports. However, the model indicates low trade volumes for combinations of countries in the SADC region. In particular, there is increasing scope of non-SACU countries to increase their exports to South Africa.